Experience of resources management on coronavirus disease 2019 epidemic at a tertiary medical center in Northern Taiwan. Issue 5 (30th April 2021) - Lan, Kai-Ping; Hsu, Yueh-Shuang; Chang, Ching-I; Wei, Pi-Ching; Guo, Ti-Gen; Yen, David Hung-Tsang; Hsu, Teh-Fu; Tzeng, Yuann-Meei; Ming, Jin-Lain
Abstract : Background: Coronavirus disease 2019 (COVID-19) is a respiratory infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes infectious symptoms including fever, cough, respiratory and gastrointestinal symptoms, and even loss of smell/taste and to date had caused 489 000 people to be infected with 32 000 deaths. This article aims to develop some strategies in dealing with the COVID-19 epidemic to prevent nosocomial infection and ensure the safety of healthcare workforce and employees. Methods: This is a prospectively registered and retrospective descriptive study investigating the clinical characteristics, results of diagnostic tests, and patients' disposition from February 1, 2020, to April 30, 2020, at a tertiary medical center in Northern Taiwan. Results: There is no nosocomial spreading of SARS-CoV-2 in our facility. The following strategies were followed: information transparency; epidemic prevention resources planning by authorities; multidisciplinary cooperation; informative technologies; immigration quarantine policies; travel restrictions; management of diversion/subdivision; self-health monitoring; social distancing; screening of travel, occupation, contact, and cluster (TOCC) history; traffic control bundling (TCB); training of using personal protective equipment; real-name visiting management; and employee care. The patients' basic characteristics and diagnostic results were gathered. Of the 3832 cases, about 25.9% had travel history. Most of them were traveling to Asia (419 people/time, 10.9%) and from China (256 people/time, 6.7%). Meanwhile, healthcare personnel accounted for 316 people/time (8.3%) and cleaning personnel, 6 people/time (0.16%). The 36 cases who care or have contact with confirmed cases have negative results from the COVID-19 test. The most frequent symptoms were fever and upper respiratory infection followed by gastrointestinal symptoms. Conclusion: The above strategies were followed. Patients were stratified based on the risk of TOCC history assessment to ensure the safety of healthcare personnel and patients' appropriate and timely medical services.